Keabsahan Kontrak Elektronik dalam Perjanjian Jual Beli, Ditinjau dari Perspektif Pasal 1313 KUHPerdata - Elyviatino, Elsha Putri; Nugroho, Lucky Dafira (AHKAM, 2025)
Electronic contracts play a crucial role in modern business transactions in the digital era, yet their legal validity remains a subject of debate within the context of Indonesian law. This study aims to analyze the validity of electronic contracts based on national legal provisions. A normative juridical approach was employed, using data obtained through literature review, statutory regulations, and court decisions. The findings show that electronic contracts are legally recognized in Indonesia as long as they fulfill the essential elements of a valid agreement as stipulated in Law Number 11 of 2008 on Electronic Information and Transactions (UU ITE), including mutual consent, legal capacity, a specific object, and a lawful cause. Although electronic contracts are normatively grounded in a strong legal framework, their implementation continues to face challenges such as low public awareness of their legality and benefits, as well as limitations in digital infrastructure. Therefore, strategic measures are necessary to enhance public understanding, strengthen digital legal literacy, and develop adequate supporting infrastructure to effectively and sustainably optimize the implementation of electronic contracts in legal practice and socio-economic life.